Code of the hills [large type] - Offutt, Chris, 1958- (Offutt, Chris, 1958- Mick Hardin novels, 2023)
"Mick Hardin is back in the hills of Kentucky. He'd planned to touch down briefly before heading to France, marking the end of his twenty-year Army career. In Rocksalt, his sister Linda the sheriff is investigating the murder of Pete Lowe, a sought-after mechanic at the local racetrack. After another body is found, Linda and her deputy Johnny Boy Tolliver wonder if the two murders are related. Linda steps into harm's way just as a third body turns up and Mick ends up being deputized again, uncovering evidence of illegal cockfighting, and trying to connect all the crimes" --